Differences in bioavailability and tissue accumulation efficiency of (all-E)- and (Z)-carotenoids: A comparative study. (1st November 2021) - Honda, Masaki; Takasu, Soo; Nakagawa, Kiyotaka; Tsuda, Takanori
Highlights: Differences in bioavailability and tissue accumulation efficiency of (all- E )- and ( Z )-carotenoids were evaluated in rats. Three commercially important carotenoids (lycopene, β-carotene, and lutein) were evaluated. Z -Isomer-rich carotenoids were prepared from the all- E -isomers by thermal treatment. Carotenoid Z -isomers had higher bioavailability and tissue accumulation efficiency than the all- E -isomers. Feeding of Z -isomer-rich carotenoids enhanced the Z -isomer ratio in plasma and tissues. Abstract: This study investigated the differences in bioavailability and tissue accumulation efficiency between all- E - and Z -isomer-rich carotenoids after oral administration to rats. Three commercially important carotenoids (lycopene, β-carotene, and lutein) were chosen for the study. For all carotenoids, feeding with Z -isomer-rich diets increased their concentrations in plasma and tissues at least similar to or more than the all- E -isomer-rich diets, e.g., in rats fed a Z -isomer-rich lycopene, the lycopene concentrations in the plasma and liver after the 2-week administration were respectively 6.2 and 11.6 times higher than those fed an all- E -isomer-rich diet. These results strongly indicate that carotenoid Z -isomers have higher bioavailability and tissue accumulation efficiency than the all- E -isomers. Moreover, diets rich in carotenoid Z -isomers significantly improved the total Z -isomer ratio in plasma and several tissues compared to the all- E -isomers. Since carotenoid Z -isomers potentially have higher antioxidant activity than the all- E -isomers, their accumulation in the body might bring remarkable health benefits.